Ferric oxide as a support of carbide slag for effective transesterification of triglycerides in soybean oil. (15th October 2019) - Liu, Mengqi; Huang, Ying; Liu, Qianhe; Hu, Xun; Liu, Qing; Chen, Haokai; Dong, Yinjie; Zhao, Yanran; Niu, Shengli
Graphical abstract: Highlights: Fe2 O3 addition improved performances of carbide slag for transesterification. CS/Fe2 O3 from FeCl3 showed superior catalytic activity due to developed pore structure. Ca2 Fe2 O5 was formed from solid phase reaction of CaO and Fe2 O3 . CaO and Ca2 Fe2 O5 coordinately promoted the catalytic activity of CS/Fe2 O3 . The presence of Fe2 O3 promoted the catalytic stability of CS/Fe2 O3 . Abstract: In this study, carbide slag loaded on ferric oxide (CS/Fe2 O3 ) was synthesized as the catalyst for the transesterification of the soybean oil to biodiesel. The results indicated that CS/Fe2 O3 catalyst showed superior catalytic activity and stability for the transesterification, which was related to the formation of Ca2 Fe2 O5 phase in the catalyst. In addition, the catalytic activity of CS/Fe2 O3 was also affected by the precursors of the support and the molar ratio of calcium and iron in the catalyst. The catalyst with ferric chloride as the precursor performed the best catalytic performance, which was associated with the smallest mean pore diameter and the largest specific area. In addition, ferric oxide as a support could improve the stability of the CS/Fe2 O3 . Physical and chemical indexes of the produced biodiesel were analyzed and the results showed that the properties of the fuel met the requirement of the American Society for Testing Materials standard to be used as a green alternative source of the diesel.